1999
DOI: 10.1212/wnl.52.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine

Abstract: These results demonstrate that oxcarbazepine given as monotherapy is effective and safe for the treatment of partial seizures in this paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 5 publications
2
81
0
1
Order By: Relevance
“…These results are confirmed by other monotherapy and adjunctive therapy studies in similar refractory patient populations (9,10,20) and provide evidence that 2400 mg/d OXC is a very effective dosage. The efficacy results from this study also indicate that OXC and CBZ appear to have different mechanisms of action, because 74% of patients in this study were already on CBZ and received additional benefit when OXC was added.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These results are confirmed by other monotherapy and adjunctive therapy studies in similar refractory patient populations (9,10,20) and provide evidence that 2400 mg/d OXC is a very effective dosage. The efficacy results from this study also indicate that OXC and CBZ appear to have different mechanisms of action, because 74% of patients in this study were already on CBZ and received additional benefit when OXC was added.…”
Section: Discussionsupporting
confidence: 76%
“…To investigate potential interactions with plasma MHD concentrations, ratios of mean steady-state (visits [6][7][8][9][10][11][12] to mean baseline (visits 1-3) plasma concentrations were calculated for each of the following concomitant AEDs: CBZ, valproic acid, phenobarbital, PHT, vigabatrin, clobazam, lamotrigine, clonazepam, primidone, diazepam, and gabapentin. Blood samples to determine trough plasma MHD concentrations were collected before the morning drug dose at visits 3, 6, 7, 9, 11, and 12. Approximately 7 mL of venous blood were collected and centrifuged at room temperature immediately after collection.…”
Section: Pharmacokinetic End Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ethical issues on the use of placebo in such an experimental monotherapy situation remain. 25 Another variation of the newly diagnosed monotherapy design aimed at demonstrating a difference is to recruit a more generalized population with fewer seizures since diagnosis (and either no treatment or no chronic treatment) and randomize the patients into two groups: a good dose and a dose thought to be marginally effective (if effective at all). The analysis uses the time to n th -seizure as the primary outcome variable.…”
Section: Monotherapy Trialsmentioning
confidence: 99%
“…Schacter et al (24) reported the first randomized, double-blind, placebo-controlled monotherapy study that involved 102 presurgical patients hospitalized at 10 United States epilepsy centers. Patients completed routine presurgical evaluation for refractory epilepsy after two to ten partial seizures and were off AEDs (except for lorazepam) for at least 48 h before randomization to monotherapy with OXC (rapidly titrated to 2,400 mg/day by day 2) or placebo.…”
Section: Adverse Events R Pht V Oxc In Adultsmentioning
confidence: 99%